A review on carbon dots: synthesis, characterization and its application in optical sensor for environmental monitoring - Omar, Nur Alia Sheh (MDPI, 2022)
The development of carbon dots (CDs), either using green or chemical precursors, has inevitably led to their wide range application, from bioimaging to optoelectronic devices. The reported precursors and properties of these CDs have opened new opportunities for the future development of high-quality CDs and applications. Green precursors were classified into fruits, vegetables, flowers, leaves, seeds, stem, crop residues, fungi/bacteria species, and waste products, while the chemical precursors were classified into acid reagents and non-acid reagents. This paper quickly reviews ten years of the synthesis of CDs using green and chemical precursors. The application of CDs as sensing materials in optical sensor techniques for environmental monitoring, including the detection of heavy metal ions, phenol, pesticides, and nitroaromatic explosives, was also discussed in this review. This profound review will offer knowledge for the upcoming community of researchers interested in synthesizing high-quality CDs for various applications.